2017
DOI: 10.1016/j.cmet.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cold Adaptation Does Not Require FGF21 or UCP1

Abstract: Brown adipose tissue (BAT)-dependent thermogenesis and its suggested augmenting hormone, FGF21, are potential therapeutic targets in current obesity and diabetes research. Here, we studied the role of UCP1 and FGF21 for metabolic homeostasis in the cold and dissected underlying molecular mechanisms using UCP1-FGF21 double-knockout mice. We report that neither UCP1 nor FGF21, nor even compensatory increases of FGF21 serum levels in UCP1 knockout mice, are required for defense of body temperature or for maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
80
5

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 45 publications
16
80
5
Order By: Relevance
“…The disconnect between thermogenic genes and cold tolerance in the current study supports other work showing that browning is not necessary for thermoregulation or the regulation of whole‐body glucose and lipid metabolism (1, 28, 4044). For example, large increases in iWAT Ucp1 expression following chronic treatment with CL316,243 are not associated with increased glucose or fatty acid uptake by this tissue (29).…”
Section: Discussionsupporting
confidence: 90%
“…The disconnect between thermogenic genes and cold tolerance in the current study supports other work showing that browning is not necessary for thermoregulation or the regulation of whole‐body glucose and lipid metabolism (1, 28, 4044). For example, large increases in iWAT Ucp1 expression following chronic treatment with CL316,243 are not associated with increased glucose or fatty acid uptake by this tissue (29).…”
Section: Discussionsupporting
confidence: 90%
“…6, our results suggest that the Fgf21‐Ucp1 axis is engaged by MD only in male mice, and may be dispensable for the metabolic benefits of MD in females as female mice derive these benefits despite unchanged plasma Fgf21 levels and Ucp1 gene expression. Alternatively, MD may promote metabolic health in both sexes through Fgf21‐Ucp1–independent mechanisms, as was recently found to be true in the case of cold‐induced thermogenesis (48, 49). Our results have also revealed sexually dimorphic effects of MD on hepatic gene expression, particularly with respect to the regulation of lipid metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…This observation suggests that although mice of both sexes fed MD diets have increased energy expenditure, the mechanism linking MR to increased energy expenditure may be independent of Fgf21 and Ucp1 , at least in females. Recent work has demonstrated that cold‐induced thermogenesis is also mediated by a Fgf21‐Ucp1 independent mechanism (48, 49). Further research is needed to specifically identify the biologic basis for the increased energy expenditure induced by MD in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The Seahorse Extracellular Flux Analyzer is a prevalent approach to measuring the oxygen consumption rate (OCR) of isolated adipocytes [11,12], and it has been reported that the OCR of brown adipocytes increases after the activation of thermogenesis by norepinephrine (NE) treatment [13]. Other measurements such as blood flow, food intake and locomotor activity [19][20][21] are all short of specificity and are incapable of distinguishing the metabolism of brown and beige fat from that of the entire organism. Thermal imaging allows noninvasive measurement of the temperature change in BAT during thermogenesis.…”
Section: Introductionmentioning
confidence: 99%